2009
DOI: 10.4049/jimmunol.0803899
|View full text |Cite
|
Sign up to set email alerts
|

Murine B Cell Response to TLR7 Ligands Depends on an IFN-β Feedback Loop

Abstract: Type I IFNs play an important, yet poorly characterized, role in systemic lupus erythematosus. To better understand the interplay between type I IFNs and the activation of autoreactive B cells, we evaluated the effect of type I IFN receptor (IFNAR) deficiency in murine B cell responses to common TLR ligands. In comparison to wild-type B cells, TLR7-stimulated IFNAR−/− B cells proliferated significantly less well and did not up-regulate costimulatory molecules. By contrast, IFNAR1−/− B cells did not produce cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 50 publications
8
100
0
1
Order By: Relevance
“…It has been shown that IFNAR signals play important roles in regulating TLR7 responses in both human and mouse B cells, contributing to the roles played by TLR7 in both normal immunity and autoimmunity (12)(13)(14). In this study, we demonstrated a novel role for the IFNAR in regulating TLR7 responses in B cells.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…It has been shown that IFNAR signals play important roles in regulating TLR7 responses in both human and mouse B cells, contributing to the roles played by TLR7 in both normal immunity and autoimmunity (12)(13)(14). In this study, we demonstrated a novel role for the IFNAR in regulating TLR7 responses in B cells.…”
Section: Discussionmentioning
confidence: 49%
“…TLR expression (35). In B cells, IFNAR signals are shown to induce increased TLR7 expression (14). However, our findings show that TLR7 expression was not decreased in tolerant B cells.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations